Corporate Governance's Role in Shaping Tax Avoidance Strategies - Peter Winarta; Yuniarwati (Облік і фінанси)
Companies are increasingly resorting to tax avoidance, a strategy aimed at reducing the tax burden within the law, to accumulate more capital. Understanding the drivers of tax avoidance is crucial for both regulatory bodies and businesses, particularly in a climate of heightened scrutiny of corporate behaviour. This study examines the intricate relationships between profitability, solvency, good corporate governance (GCG), and tax avoidance. The study focuses on firms in the energy sector listed on the Indonesia Stock Exchange (IDX) between 2021 and 2023. The research adopts a quantitative design, which allows for examining causal relationships between variables. The study examines how tax avoidance is impacted by profitability and solvency as independent factors, with sound corporate governance serving as a moderating variable. The information used for analysis came from secondary sources, specifically the audited annual financial statements of the selected energy sector companies, which were accessed from the IDX website. Structural Equation Modeling (SEM) with a Partial Least Squares (PLS) approach was employed for data analysis. he findings indicate that profitability has a significant negative impact on tax avoidance, while solvency exhibits a positive but insignificant effect. Furthermore, good corporate governance does not mitigate the association between tax avoidance and profitability or solvency. This research provides valuable insights for financial management within the energy sector, emphasizing the need for a deeper comprehension of the relationship between tax avoidance and profitability and solvency, alongside the necessity for good corporate governance practices to enhance transparency, and suggests that tax regulations should be adjusted to account for the effects of profitability on tax avoidance behaviour. The results suggest that, despite the limited influence of governance mechanisms in moderating tax avoidance, companies should still strive to enhance governance practices and transparency. By integrating strong tax compliance measures and a commitment to ethical conduct, companies can reduce their exposure to the reputational and legal risks associated with tax avoidance, even if governance does not directly moderate their tax behaviours.